Study of hypoglycemic activity of Tinospora cordifolia in alloxan induced diabetic rabbits - Tamboli, Saleem B.; Sontakke, Sumit P.; Parsode, Rahul B. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: This study was designed to investigate the hypoglycemic effect of Tinospora Cordifolia in alloxan-induced diabetic rabbits. Methods: Rabbits were divided into four experimental groups: Non-diabetic rabbits treated with normal saline, Non-diabetic rabbits treated with TCREt, Diabetic rabbits treated with Metformin, Diabetic rabbits treated with TCREt. Treatment with drugs was started on the 8th day of alloxan treatment (i.e. day 1) and was continued for 30 days. Statistical evaluation was done using student’s ‘t’ test & one way ANOVA followed by Tuckey`s post hoc test. ‘p’ value less than 0.05 was considered statistically significant. Results: TCREt showed hypoglycemic action in alloxan induced diabetes rabbits. It did not produce hypoglycemia in non diabetic rabbits. Conclusion: Hypoglycemic action of TCREt is comparable to that of standard oral hypoglycemic drug metformin.